The effect of using data mining techniques on the efficiency of internal auditing in light of the use of resource planning systems (Journal of the College of Basic Education, 2022)
As a result of the tremendous development in information technology and reliance on resource planning systems, the need to perform the internal audit function has increased by people with the expertise, skills and technical knowledge required for auditing. Where the research focused on studying the effect of using resource planning systems on the efficiency of internal auditing, as well as the effect of using data mining techniques and resource planning systems on the efficiency of internal auditing. To test the results of the research hypotheses, a questionnaire was designed and distributed to the study population. The results of the research showed that there is a great agreement between the internal auditors about changing the current internal audit system, as there was a statistically significant impact of the application of resource planning systems on the efficiency of internal auditing, and a statistically significant effect was found for the application of data mining techniques and resource planning systems on the efficiency of internal auditing. By relying on important and accurate information as quickly as possible.